Firewalls for dummies - Komar, Brian (Wiley, 2003)
Includes material on setting up firewalls for SOHO and creating demilitarized zones. Also includes material for deploying firewall solutions using Windows, Linux, ZoneAlarm, BlackICE, Norton Personal Firewall, Microsoft Internet Security and Acceleration 2000, and Check Point FireWall-1 Next Generation.
Keywords: Firewalls (Computer security); Datensicherung; Rechnernetz; TCP/IP; Internet; Firewall; Einführung